Transformasi Fungsi Alat Batu Semu Situs Gunungwingko - Goenadi Nitihaminoto (Balai Arkeologi Yogyakarta, 1995)
Gunungwingko Site stone tools consist of two types, namely pseudo stone tools and stone tools. Both types of tools were found in the context of burials. In relation to the context of the findings, the function of the two types of stone tools is thought to be a complementary function of the ceremony or as a ceremonial object that had previously served as a practical tool. As a practical tool, the Gunungwingko pseudo stone tool is characterized by several uses such as being used as a batting tool, an anvil tool, and as a scrubbing tool. Meanwhile, the non-pseudo stone tool consists of a proto adze, which is practically unused.